Rečnik Samjuela Džonsona (Philologia, 2021)
This text is written to mark the 300th anniversary of Samuel Johnson’ birth, and it deals with Johnson’s Dictionary of the English Language. In The Plan of a Dictionary of the English Language Johnson outlined his intentions and the methods he was going to use while compiling the dictionary, but in the Preface of the first edition published in 1755, he admitted that during the seven-year work he became aware of the realities of his task and had to give up the prescriptive role. Despite the weaknesses of his work, and negative attitudes that some of his contemporaries expressed, Johnson’s Dictionary was the first dictionary compiled on lexicographic principles. It was considered a standard of the English language and was widely used for decades.
Keywords: rečnik; leksikografija; standard; engleski jezik